Visual and Keratometric Results after Corneal Collagen Cross Linking in Keratoconus - Yasir Iqbal, Mirza Inamul Haq, Aneeq Ullah Baig Mirza (Pakistan Journal of Ophthalmology, 2018)
Purpose: To evaluate the safety and efficacy of riboflavin – ultraviolet type A light rays induced cross-linking of corneal collagen in keratoconus. Material and Methods: Forty cases of collagen cross-linking were studied retrospectively. Preoperative examination included uncorrected and bestcorrected visual acuity, refraction, slit-lamp, fundoscopy and orbscan. Routine cross-linking procedure was performed. Postoperatively, a bandage contact lens was applied which was removed on the 5th day. Subsequent postoperative examinations were performed monthly for six months. Results: Forty cases completed six months of follow up. There were 21 males and 19 females in the study. The age range was 16-32 years. In the six months study, 13 out of 40 cases showed improvement of un-corrected visual acuity by one line and 15 out of 40 had improvement by 2 or more lines. Only two eyes out of 40 (5%) lost 2 or more lines of uncorrected visual acuity. Keratometric improvement was seen in 22.5%. 65% showed keratometric stability while progression was seen in 12.5%. Conclusion: Collagen cross – linking is a safe and effective procedure in halting the progression of keratoconus.